Observed and Modeled Mountain Waves from the Surface to the Mesosphere near the Drake Passage - Kruse, Christopher G.; Alexander, M. Joan; Hoffmann, Lars; van Niekerk, Annelize; Polichtchouk, Inna; Bacmeister, Julio T.; Holt, Laura; Plougonven, Riwal; Šácha, Petr; Wright, Corwin; Sato, Kaoru; Shibuya, Ryosuke; et al. (Journal of the atmospheric sciences, 2022)
Four state-of-the-science numerical weather prediction (NWP) models were used to perform mountain wave (MW)-resolving hindcasts over the Drake Passage of a 10-day period in 2010 with numerous observed MW cases. The Integrated Forecast System (IFS) and the Icosahedral Nonhydrostatic (ICON) model were run at Δ x ≈ 9 and 13 km globally. The Weather Research and Forecasting (WRF) Model and the Met Office Unified Model (UM) were both configured with a Δ x = 3-km regional domain. All domains had tops near 1 Pa ( z ≈ 80 km). These deep domains allowed quantitative validation against Atmospheric Infrared Sounder (AIRS) observations, accounting for observation time, viewing geometry, and radiative transfer. All models reproduced observed middle-atmosphere MWs with remarkable skill. Increased horizontal resolution improved validations. Still, all models underrepresented observed MW amplitudes, even after accounting for model effective resolution and instrument noise, suggesting even at Δ x ≈ 3-km resolution, small-scale MWs are underresolved and/or overdiffused. MW drag parameterizations are still necessary in NWP models at current operational resolutions of Δ x ≈ 10 km. Upper GW sponge layers in the operationally configured models significantly, artificially reduced MW amplitudes in the upper stratosphere and mesosphere. In the IFS, parameterized GW drags partly compensated this deficiency, but still, total drags were ≈6 times smaller than that resolved at Δ x ≈ 3 km. Meridionally propagating MWs significantly enhance zonal drag over the Drake Passage. Interestingly, drag associated with meridional fluxes of zonal momentum (i.e., ) were important; not accounting for these terms results in a drag in the wrong direction at and below the polar night jet.